Evaluating Participatory Practice In archaeology: Proposal for a standardized approach. Issue 2 (3rd April 2022) - Tully, Gemma; Anés, Lara Delgado; Thomas, Suzie; Olivier, Adrian; Benetti, Francesca; Mena, Alicia Castillo; Arnau, Alexandra Chavarria; Rizner, Mia; Möller, Katharina; Karl, Raimund; Matsuda, Akira; Martín Civantos, José María; et al.
ABSTRACT: In this paper we present a proposal for the creation of a standardized evaluation model for participatory/public/community archaeology and heritage initiatives. The proposal is the result of discussions during a Spring School that the University of Padua and the MAG Museum of Alto Garda, Italy, organized between 9 and 15 April 2018. The Spring School brought together international practitioners to compare experiences and share visions for the sustainable future of archaeology and heritage management. We reflect on the process of bringing together our thoughts and views into one place, and on the theoretical and practitioner contexts that inform our proposed model. The model is intended for researchers and practitioners planning to carry out archaeological and heritage projects with communities. We invite readers to try using some or all of the sections of the model in their own work and to contribute to further refinement of the approach.